Identifying the Most Common CrossFit Injuries in a Variety of Athletes. (January 2020) - Alekseyev, Kirill; John, Alex; Malek, Andrew; Lakdawala, Malcolm; Verma, Nikhil; Southall, Colton; Nikolaidis, Argyrios; Akella, Sudheer; Erosa, Samantha; Islam, Rayeed; Perez-Bravo, Efrain; Ross, Marc
Background: CrossFit is an increasingly popular, rapidly growing exercise regimen. Few studies have evaluated CrossFit-associated musculoskeletal injuries on a large scale. This study explores such injuries and associated risk factors in detail. Objective: To identify the most common musculoskeletal injuries endured during CrossFit training among athletes at different levels of expertise. Design: Survey-based retrospective cross-sectional study. Setting: Distribution at CrossFit gyms in the United States and internationally. Also published on active online forums. Participants: A total of 885 former and current CrossFit athletes. Methods: Institutional review board-approved 33-question Web-based survey focused on CrossFit injuries and associated risk factors. Survey submissions were accepted for a period of 6 months. Main outcome measurements: Specific injuries with associated workouts, risk factors that affected injury including (1) basic demographics, (2) regional differences in reported injuries, (3) training intensity, and (4) expertise level at time of injury. Results: Of the 885 respondents, 295 (33.3%) were injured. The most common injuries involved the back (95/295, 32.2%) and shoulder (61/295, 20.7%). The most common exercises that caused injury were squats (65/295, 22.0%) and deadlifts (53/295, 18.0%). Advanced-level (64/295, 21.7%) athletes were more significantly injured than beginner-level (40/295, 13.6%) athletes. International participants were 2.2 times more likely than domestic US participants to suffer injury. Individuals with 3+ years of CrossFit experience were 3.3 times more likely to be injured than those with 2 or less years of experience. Participants who trained for 11+ h/week were significantly more likely to be injured than those who trained less than or equal to 10 h/week. Conclusions: As CrossFit becomes more popular, it is important to monitor the safety of its practitioners. Further studies are needed to explore how to lower this injury prevalence of 33.3%. Areas to focus on include factors that have caused the regional (international vs US states) differences, level of expertise/experience differences (advanced level vs intermediate and beginner levels), and stretching routine modifications.